EVALUASI KESESUAIAN LAHAN UNTUK BUDIDAYA JERUK KEPROK (CITRUS RETICULATA) BERBASIS SISTEM INFORMASI GEOGRAFI DI KECAMATAN KUALIN KABUPATEN TIMUR TENGAH SELATAN - Metboki, Stending; Samin, Mikael; Rahmawati, Arfita (Jurnal Geografi, 2022)
Tangerines have become iconic in South Central Timor Regency. However, in Kualin District, production has been decreasing in the last five years. Cultivation of this plant requires special geographical factors. The role of geographic information systems can support both aspects of analysis, manipulation, and presentation. This study aims to determine the area of land class for the cultivation of tangerines in Kualin District using a geographic information system. This study uses a quantitative descriptive method. The data analysis technique used to determine land suitability is the matching method or the matching of each land characteristic. The data collection technique used in this study is to interpret remote sensing images and secondary data, then overlay them so that they provide four levels of conformity, namely very suitable (S1), suitable (S2), less suitable (S3) and not suitable (N). . The results of the study are as follows: 1. Map overlay analysis shows that most of the area has unsuitable land (S3) with an area of 121.08 km2 (59.62 %), land that is quite suitable (S2) is 87.32 km2 (40, 05 %), very unsuitable area (N) was 0.62 km2 (0.32 %) and for very suitable area (S1) it was only 0.02 km2 or 0.01% of the total area of Kualin District.